Measurement of the inclusive isolated prompt photon cross-section in pp collisions at √s = 7 TeV using 35 pb-1 of ATLAS data - Anduaga, Xabier Sebastián (2011)
A measurement of the differential cross-section for the inclusive production of isolated prompt photons in pp collisions at a center-of-mass energy √s = 7 TeV is presented. The measurement covers the pseudorapidity ranges |η| < 1.37 and 1.52 ≤ |η| < 2.37 in the transverse energy range 45 ≤ ET < 400 GeV. The results are based on an integrated luminosity of 35 pb-1, collected with the ATLAS detector at the LHC. The yields of the signal photons are measured using a data-driven technique, based on the observed distribution of the hadronic energy in a narrow cone around the photon candidate and the photon selection criteria. The results are compared with next-to-leading order perturbative QCD calculations and found to be in good agreement over four orders of magnitude in cross-section.